Limitation of shipowners' liability - Field, Roger Francis (Institute of Marine and Environmental Law, 2023)
Consideration is given firstly to the origins of the principle of a shipowner being entitled to limit his liability to third parties who have suffered loss or injury as a result of the negligent navigation or management of his ship noting that the principle evolved as a matter of public policy designed to encourage shipping and trade. The various attempts at reaching international unity are then reviewed by way of reference to the 1924, 1957 and 1976 Conventions on Limitation of Shipowners' Liability including comment on the separate limitation regimes introduced by the Hague and Hague-Visby Rules in respect of the carriage of goods by sea. e the adoption of the principle of limitation into the South African law with the coming into force as at 1960 of the Merchant Shipping Act is then considered, it being noted here that the relevant provisions of No. 57 of 1951 reflect, rather than repeat the (then) corresponding provisions in the English law following on the adoption and enactment by that country of the 1957 Limitation Convention. The word reflect is used advisedly as South Africa is neither a signatory to nor has it adopted the 1957 Convention per se resulting in a measure of uncertainty and difficulty when it comes to the application of the relevant provisions of the Act. These provisions viz. s 261 et seq are then dealt with in some detail with consideration being given to such matters as to who may limit their liability, what ships are subject to limitation, the amounts of limitation and how these are. calculated with reference to a ship's tonnage etc. e Finally under this Part, the question of which claims are subject to limitation and which, by way of separate legislative enactment, are not subject to limitation, is examined. PART B: Pages 21 to 42 This Part is devoted to the loss of the right to limit liability with an in-depth look being taken at the meaning of the words "actual fault or privity". Here particular attention is paid to the interpretation of the personalised requirement of s 261 (whose actual fault or privity are we concerned with etc.?) and what degree of culpability the words connote. Given the dearth of reported South African cases, the approach of van Heerden Jin The "SAINT PADARN", 1986 ( being the only South African case to date dealing with the subject) is followed by way of having regard to a number of the leading English cases commencing with Lennard's case of 1915 through the well-known "LADY GWENDOLEN" case of 1965 and the "new approach" introduced. by it and beyond to the House of Lords decision in the "MARION", 1984.